Differentiation of Bovine and Porcine Gelatins in Soft Candy Based on Amino Acid Profiles and Chemometrics - Raraswati, Mita Amalia; Triyana, Kuwat; ., Triwahyudi; Rohman, Abdul (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
Gelatin is widely used in some food products, including soft candy (one of food products preferred by children). Most of the gelatin available in the market derived from pigs. Some religions like Islam and Jews prohibited their followers to consume any food products containing pig derivatives, including porcine gelatin. Therefore, it is necessary to develop some rapid and reliable methods for detection of porcine gelatin in soft candy. The purpose of this study was to differentiate and classification the gelatin sources (porcine or bovine) in soft candy based on amino acid profiles combined with chemometrics of principal component analysis (PCA). Separation and determination of amino acid was conducted by reversed-phase HPLC using a fluorescent detector, after being derivatized Â with ortho-phtalaldehyde in 2-mercaptoethanol (OPA/2-MCE). Parameters of peak height percentage of each amino acids from each sample were analyzed by PCA. Based on PC1 and PC2, porcine and bovine gelatins in soft candy could be apparently distinguished.